Perencanaan Strategis SI/TI untuk Meningkatkan Keunggulan Kompetitif. - Alfredo Kristian; Viola Putri Meylani; Nickolas Su; Roger Skavinsky Teddy; Dicky Pratama (Universitas Methodist Indonesia, 2025)
Strategic planning for information systems and information technology (IS/IT) is a vital process for organizations to achieve business goals amidst global competition and rapid technological advancements. This planning aims to align business strategies with IS/IT development to improve operational efficiency, help better decision making, and create a competitive advantage. This article examines the significance of IS/IT strategic planning using a literature review approach to identify key success factors, such as business needs analysis, evaluation of existing technological capabilities, and innovation-driven strategy execution. The findings reveal that organizations effectively implementing IS/IT strategic planning can adapt to market changes and leverage technology as a key driver of business success. This article provides practical insights for stakeholders to design integrated and sustainable IS/IT strategic plans.